2012
DOI: 10.1128/iai.00069-12
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-Scanning Mutagenesis Supports the Importance of Clostridium perfringens Enterotoxin Amino Acids 80 to 106 for Membrane Insertion and Pore Formation

Abstract: Clostridium perfringens enterotoxin (CPE) causes the gastrointestinal symptoms of the second most common bacterial foodborne illness. Previous studies suggested that a region named TM1, which has amphipathic characteristics and spans from amino acids 81 to 106 of the native CPE protein, forms a ␤-hairpin involved in ␤-barrel pore formation. To further explore the potential role of TM1 in pore formation, the single Cys naturally present in CPE at residue 186 was first altered to alanine by mutagenesis; the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…Furthermore, those structural analyses, coupled with mutagenesis studies (56)(57)(58)(59)(60)(61), indicated that CPE contains a C-terminal domain that binds to claudin receptors on host cells and an N-terminal domain, consisting of two halves, that is critical for pore formation by mediating oligomerization and membrane insertion.…”
Section: Toxins That Can Be Either Chromosomally or Plasmid Encodedmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, those structural analyses, coupled with mutagenesis studies (56)(57)(58)(59)(60)(61), indicated that CPE contains a C-terminal domain that binds to claudin receptors on host cells and an N-terminal domain, consisting of two halves, that is critical for pore formation by mediating oligomerization and membrane insertion.…”
Section: Toxins That Can Be Either Chromosomally or Plasmid Encodedmentioning
confidence: 99%
“…In addition to six copies of the toxin, CH-1 contains both receptor and nonreceptor claudins (the presence of nonreceptor claudins in CH-1 likely reflects a propensity for claudin-claudin interactions) (66). The CH-1 prepore complex, which forms in both cultured Caco-2 cells and the small intestine, then inserts into membranes by using a ␤-hairpin formed by CPE amino acids 81 to 106 (59,61). This process results in formation of a cation-selective CPE pore that is initially permeable to molecules of Ͻ200 Da (1,(75)(76)(77).…”
Section: Toxins That Can Be Either Chromosomally or Plasmid Encodedmentioning
confidence: 99%
“…The protease sensitivity of oligomerized CPB complex present on the surface of HUVEC cells was assayed using a modification of previously described methods (27). Briefly, HUVEC cells were cultured in 6-well plates until confluent monolayers were achieved.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of a functional CPB pore was assessed by measuring 86 Rb release from host cells, as described previously (27). Briefly, 24-well plates were seeded with HUVEC cells and grown to confluent monolayers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation